Report of the Seminar on Nigeria in Transition - Nigeria (Lagos : Federal Ministry of Information, 1980)
This book is a seminar in transition being organized toward the end of the military administration
Cover title: Nigeria in transition.
Includes bibliographical references.
oo 23/01/2019
Loans
Keywords: Nigeria; Nigeria